Priorities for sustainable turfgrass management: a research and industry perspective - Strandberg, M.; Blombäck, K.; Dahl Jensen, A. M.; Knox, Jerry W. (Taylor and Francis, 2012)
This paper provides a brief review and assessment of the key environmental, regulatory and technical issues facing the turfgrass sector with specific reference to the European context. It considers the range of externalities or ‘drivers for change' facing the industry, and the challenges and opportunities available for promoting and achieving more sustainable turfgrass management within the sports, landscape and amenity sectors. The analysis confirms that there are a number of key areas where a concerted research and industrial effort is required. These include responding to the pressures from government demands for greater environmental regulation, the increasing pressure on natural resources (notably water, energy and land), the emerging role of turf management in supporting ecosystem services and enhancing biodiversity, the continued need to promote integrated pest management, and the looming challenges posed by a changing climate, and urgent need to adapt. Whilst many of these externalities appear to be risks to the sports turf industry, there will also be significant opportunities, for those where the labour, energy and agronomic costs are minimized and where the drive to adopt a multifunctional approach to sportsturf management is embraced.
Keywords: Ecosystem services; Golf courses; Integrated pest management; Landscape amenity; Natural resources; Sport fields